Analysis of Heat Recovery System Performance Using a Serpentine-Type Heat Exchanger on Water Heater with Fins Number Variation - I Gusti Agung Gede Kusuma Artha; Made Sucipta; Hendra Wijaksana (Natural Sciences Engineering and Technology Journal, 2023)
The water heater is a common facility found in hotels or homes. There are alternative ways to do this besides using water heaters on the market, namely by utilizing the heat generated by the compressor and which will be discharged through the condenser, by adding a heat recovery system to the air conditioning unit. These research tests were carried out on variations of the serpentine-type heat exchanger with variations in the number of fin plates on the performance of the heat recovery system and on the split air conditioner. This research is an experimental study on a serpentine-type heat exchanger. Tests were carried out on a variety of heat exchangers with variations in the number of fin plates combined with a heat recovery system on a split AC. The independent variables in this study were three variations of the placement of the fin plate on the serpentine-type coil and the setting of the output air of the AC evaporator. Enthalpy values, refrigeration effects, compressor work, condenser, and coefficient of performance (COP) are calculated and presented in tables and graphs. The results of the performance of the heat recovery system obtained variations in the setting of the air burst coming out of the evaporator 24ºC has the highest COP value. The use of a heat recovery system can increase COP. With variations in the number of fin plates in a heat recovery system with a serpentine heat exchanger, the use of 5 fin plates has the hottest water temperature compared to the use of 3 fin plates and 1 fin plate.